2006
DOI: 10.1111/j.1468-1293.2006.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of malnutrition on survival and the CD4 count response in HIV‐infected patients starting antiretroviral therapy

Abstract: The impact that malnutrition at the time of starting antiretroviral therapy (ART) has on survival and the CD4 count response is not known. MethodsA retrospective cohort study of patients attending the national HIV referral centre in Singapore who had a CD4 count less than 250 cells/mL and a measurement of body weight performed at the time of starting ART was carried out. Demographic and clinical variables were extracted from an existing database. Body mass index (BMI) was calculated from the weight in kilogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
125
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 25 publications
15
125
2
8
Order By: Relevance
“…Those patients in WHO Clinical stage 3 were 88% times less likely to be under nourished than WHO Clinical stage 1 ART patients, this result were in contrary with the finding in Nepal [16] and also study HIV referral center in Singapore which indicated that Patients are often not diagnosed or do not commence ART until they have advanced disease [11]. The possible explanation for this finding could be patients with WHO clinical stage 3 starts ART treatment without CD4 count and get a chance to start drug early that make drug adaptation easier than stage one.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Those patients in WHO Clinical stage 3 were 88% times less likely to be under nourished than WHO Clinical stage 1 ART patients, this result were in contrary with the finding in Nepal [16] and also study HIV referral center in Singapore which indicated that Patients are often not diagnosed or do not commence ART until they have advanced disease [11]. The possible explanation for this finding could be patients with WHO clinical stage 3 starts ART treatment without CD4 count and get a chance to start drug early that make drug adaptation easier than stage one.…”
Section: Discussioncontrasting
confidence: 56%
“…Antiretroviral therapy is critical to suppression of viral replication, reduced destruction of CD4 cells, prevention of viral resistance, promotion of immune reconstitution, and slowed disease progressions [11][12][13]. Nutrient intake can improve antiretroviral absorption and tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In present study, similarly, it was found to have increased the risk of mortality. In accordance with this, a retrospective cohort study in Singapore also showed that moderate to severe malnutrition is a significant independent predictor of death in PLWHs on ART [35]. In the present study, the impact of malnutrition was seen during the early six months of initiating HAART and disappeared thereafter.…”
Section: Discussionsupporting
confidence: 72%
“…In the next few years, $US2.6 billion will be spent on SAM treatment [4,7], and therefore, novel, cheaper, culturally acceptable, efficacious, and regionally manufactured products are already in demand for this patient group [2]. RUTF have also been used in feeding programs for HIV and TB patients and evidence from low-resource settings [8][9][10][11][12][13][14] shows that HIV/TB wasting in adults is still a public health issue in Sub-Saharan Africa, despite the increasing access to antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%